COVID-19's impact on the perceived risk of ocean cruising: A best-worst scaling study of Australian consumers. Issue 1 (February 2022) - Tapsall, Suellen; Soutar, Geoffrey N; Elliott, Wendy A; Mazzarol, Tim; Holland, Jennifer
This paper investigates aspects of cruising of most concern to Australian consumers during the COVID-19 pandemic, following the shutdown of cruising globally. Using a mixed-method approach, the study asked cruisers and non-cruisers which of the risks associated with cruising were of most concern. The study found health was the most concerning risk for respondents, regardless of cruising history and, contrary to previous research, cruisers were more concerned about health risk than non-cruisers. Results indicated cruisers were also concerned about financial risk, while safety and psychological risk were the next most concerning aspects for non-cruisers. Implications for the cruise industry are discussed and areas for further research are identified. Findings suggest the industry cannot take for granted repeat cruisers' return post-pandemic. As non-cruisers are much less positive and less willing to cruise than before COVID-19, the continued future growth of the cruise sector is also under threat.